2013
DOI: 10.3109/01443615.2012.747494
|View full text |Cite
|
Sign up to set email alerts
|

Duration and determinants of inter-birth interval among women in Enugu, south-eastern Nigeria

Abstract: The difference in fertility levels of any given two societies has a relationship with the interval between births. We determined the duration of inter-birth interval and the determinants of short inter-birth interval in Enugu, Nigeria. Questionnaires were administered to a cross-section of 420 women consecutively recruited from the family planning and antenatal clinics of two hospitals in Enugu metropolis. The mean age was 30.9 ± 5.1 (range 20-44) years. The median inter-birth interval was 21.5 months and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 8 publications
9
26
2
Order By: Relevance
“…Similarly, rural residence, lack of education, being in the poorest quintile, and being Muslim were associated with a pregnancy interval of less than 24 months. The median duration of the birth to pregnancy interval in Nepal is 24 months, similar to a Nigerian study among women attending antenatal and FP clinics that showed a median interbirth interval of 21.5 months [20]. There is a need to increase the promotion of adequate spacing between pregnancies, especially among the higher risk groups (age at first birth below 20, no education, poorest quintiles, Muslims, and rural women).…”
Section: Discussionsupporting
confidence: 61%
“…Similarly, rural residence, lack of education, being in the poorest quintile, and being Muslim were associated with a pregnancy interval of less than 24 months. The median duration of the birth to pregnancy interval in Nepal is 24 months, similar to a Nigerian study among women attending antenatal and FP clinics that showed a median interbirth interval of 21.5 months [20]. There is a need to increase the promotion of adequate spacing between pregnancies, especially among the higher risk groups (age at first birth below 20, no education, poorest quintiles, Muslims, and rural women).…”
Section: Discussionsupporting
confidence: 61%
“…Enugu State has a mixed rural and urban population, most of whom are Christian and of the Igbo tribe. Further details about the study area have been provided elsewhere [12].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of poverty in the state is about 60% which implies all the associated problems of low incomes, and poor education and health [11]. Further details of the study area have been described in a recent study [13]. …”
Section: Methodsmentioning
confidence: 99%